Rancang Bangun Smart Case Sistem Monitoring Tabung Gas Elpiji Berbasis Mikrokontroler - Anisha Fadia Haya; Werman Kasoep; Nefy Puteri Novani (CHIPSET, 2020)
This study aims to create a system that can monitor gas cylinders where this device consists of two systems, the first is a system to measure the weight of 3kg LPG gas cylinders to find the remaining gas which will then be displayed on the LCD, and the second the system gives a notification (alarm) if there is a gas leak via SMS. This system consists of Arduino UNO Microcontroller components, Load cell Sensor, MQ-6 Sensor, and SIM800L GSM Module. For overall system testing, the load cell sensor system can display a percentage of the weight value obtained an error rate of 0%, this indicates that the formula used in the program runs according to what is desired. In the MQ-6 sensor system can make the buzzer on at a value >= 700 ppm, the results of the buzzer can live when the detected gas value >= 700 ppm, this is as desired. In the sim800L gsm module system can send leak notifications, the results obtained that the module can send SMS notifications. And the system turns on the buzzer when the LPG gas has reached the minimum limit, the results obtained by the buzzer will sound when the remaining gas value <= 16%. Based on tests conducted on this system the system can measure the desired weight of the cylinder to look for the remaining gas in the form of a percentage and detect a gas leak and then send an SMS notification.